2014
DOI: 10.5141/ecoenv.2014.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impacts of Argentine ant invasion of urban parks in Hiroshima, Japan

Abstract: Ant communities are well suited for monitoring changes in ecosystems. Although numerous studies have examined the responses of ant communities to environmental disturbance, relatively few long-term studies on ant communities have been undertaken in urban environments. We examined species richness in nine urban parks in Hiroshima, Japan, and compared the survey results with data collected at the same sites by using the same methods in 1999. In both surveys, total of 25 species was recorded: 23 species in 1999 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…competition (Holway, 1999;Human & Gordon, 1996). However, although negative associations were reported between several other ant species (i.e., F. japonica and Crematogaster matsumurai) and L. humile in previous studies (Miyake et al, 2002;Park et al, 2014), no associations were observed between them in this study. The difference in results may be due in part to seasonal or temporal factors and/or small sample sizes.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…competition (Holway, 1999;Human & Gordon, 1996). However, although negative associations were reported between several other ant species (i.e., F. japonica and Crematogaster matsumurai) and L. humile in previous studies (Miyake et al, 2002;Park et al, 2014), no associations were observed between them in this study. The difference in results may be due in part to seasonal or temporal factors and/or small sample sizes.…”
Section: Discussioncontrasting
confidence: 79%
“…Our GLM results for each ant species indicated decreases in P. punctatus and T. tsushimae abundance. The incidence of T. tsushimae was also reported to be clearly lower where L. humile had increased over time in several parks in Japan (Park et al, 2014). Two mechanisms have been proposed to explain the displacement of indigenous ant fauna by L. humile invasion: exploitative competition and interference L. humile on other invertebrate taxonomic groups are also not universal, and various studies have reported negative, positive, or no relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Although the host species have not been identified, the larvae of St. obsoleta have been reported to be myrmecophilous and live within ant nests (Artamonov, 2012; Bharti & Bharti, 2016). It has been demonstrated that ant communities change with urbanization in Japan (Iwata et al, 2005; Park et al, 2014; Yamaguchi, 2004, 2005; Yoshimura, 2009). One possibility for the decreasing abundance of St. obsoleta in urban areas may be due to a decrease in host availability as a result of urbanization (Corcos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The myxomycete community (i.e., of all 19 sites collectively) was analyzed by nonmetric multidimensional scaling (NMDS; Kenkel & Orlóci 1986), which is a method to examine the community structure and produces an ordination based on a dissimilarity matrix of communities, and is often used in the ecological analysis for community structure (e.g., Takahashi & Hada 2010, Park et al 2014. NMDS was performed using PAST software, based on Bray-Curtis dissimilarities (Bray & Curtis 1957).…”
Section: Discussionmentioning
confidence: 99%